2015
DOI: 10.1039/c5cc01027f
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale modelling of environmentally responsive hydrogels: emerging applications

Abstract: Stimuli-sensitive hydrogels are an exciting class of materials with widespread potential for use in engineering and biomedical applications. The design of advanced functional devices using hydrogels requires an in-depth understanding of the physics and behaviour of such materials. While theoretical tools exist, they are often limited to simple cases. Thus, computational methods are necessary to model the complex unsteady physics of hydrogels with high fidelity. Mesoscale modelling is an emerging approach that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 212 publications
0
16
0
Order By: Relevance
“…It is particularly effective in simulating complex fluids and multicomponent mixtures at the mesoscale, 48,49 like the ones presented in this work. In DPD, a volume of fluid is modeled with individual beads, where each bead represents a cluster of molecules.…”
Section: Methodsmentioning
confidence: 93%
“…It is particularly effective in simulating complex fluids and multicomponent mixtures at the mesoscale, 48,49 like the ones presented in this work. In DPD, a volume of fluid is modeled with individual beads, where each bead represents a cluster of molecules.…”
Section: Methodsmentioning
confidence: 93%
“…Dissipative Particle Dynamics (DPD) is a particle-based method which in recent years has been extensively used to study many biophysical systems [ 40 50 ]. The popularity of this method is due to several essential properties.…”
Section: Methodsmentioning
confidence: 99%
“…Using molecular dynamics simulations, these authors investigated the effect of pH on the stability of the adsorbed protein that showed no indication of denaturation under different conditions. Masoud and Alexeev (2012) used dissipative particle dynamics, a particle-based mesoscale simulation method (Yeh and Alexeev 2015), to study the controlled release of nanoparticles and macromolecules from stimuli-responsive microgels.…”
Section: Introductionmentioning
confidence: 99%